The Influence of Capital, Sensitivity, Diversification, Competition and Pandemic on Stability of Islamic Banking - Niken Septiani; Fuad Hasyim; Rais Sani Muharrami (JOURNAL OF SHARIA ECONOMICS, 2024)
Banking stability is an essential factor to measure the level of bank health. This study aims to determine the factors that influence the level of stability of Islamic Banking during the COVID-19 pandemic. ZScore provides bank stability measurement. This study uses the panel data regression analysis method with the OLS approach. Data are taken from the financial statement release of Islamic commercial banks from the first quarter of 2018 to the fourth quarter of 2022, using a purposive sampling technique and processed with E-Views 10 statistical application. The number of sampled banks was 10 banks from 13 populations. The panel data regression processing result concluded that the capital variable significantly positively affects bank stability. The sensitivity, diversification, competition, and pandemic variables do not significantly affect bank stability.